Nutrition-sensitive agri-food systems: Guidance for designing interventions in the Mekong Delta of Cambodia - International Institute of Rural Reconstruction; Bioversity International and International Center for Tropical Agriculture (2025)
Nutrition-sensitive agri-food systems (NSAFS) extend beyond food production to improve nutrition, health outcomes, and food security by enhancing the nutritional quality, accessibility, and sustainability of food systems. This Guidance was developed through a participatory process in response to stakeholder needs and contextual analyses in the Mekong Delta. It provides a structured approach for integrating nutrition objectives into the design and implementation of agri-food interventions. Targeted at government agencies, NGOs, development partners, community organizations, and research institutions, the Guidance outlines four key steps. Step 1 focuses on assessing current NSAFS conditions by examining nutrition outcomes, food consumption patterns, production and value chains, stakeholder roles, relevant interventions, and policy alignment. Step 2 involves identifying leverage points and setting nutrition-sensitive objectives, prioritizing issues that influence food accessibility, affordability, and diversity, and ensuring inclusive and appropriate agri-food activities. Step 3 emphasizes planning and implementation through coordinated partnerships, integration into local development plans, and capacity-building components. Step 4 details a participatory monitoring and evaluation (M&E) framework that measures not only agricultural outputs but also food access, dietary diversity, and health outcomes. The M&E system is designed to be context-specific, gender- and equity-focused, and aligned with national and global frameworks to ensure data consistency and policy coherence. Overall, this Guidance provides a comprehensive roadmap for strengthening NSAFS in the Mekong Delta, promoting sustainable, equitable, and nutrition-driven development.